PERTUMBUHAN BAWANG MERAH (Allium ascalonicum L.) DARI BENIH PADA BERBAGAI KONSENTRASI SUKROSA DAN KEPEKATAN MEDIA MURASHIGE DAN SKOOG - Budi Haryanto; Zainuddin Basri; Hawalina Kasim (Fakultas Pertanian, Universitas Tadulako, 2022)
The growth of explants in tissue culture media is determined by a number of factors, including the concentration of sucrose and the concentration of nutrients in the media used. The experiment was designed to determine the suitable concentration of sucrose and nutrient concentration in MS media for the growth of shallot from seeds. The experiment used a Two-factorial Completely Randomized design (CRD), namely the concentration of sucrose (30 g sucrose/l MS media, 45 g sucrose/l MS media, and 60 g sucrose/l MS media) and the concentration of MS media nutrients (0.5 times, 1 times, and 1.5 times the concentration). There were nine combinations of treatments, with each treatment repeated four times. A total of 108 shallot seeds were used in the experiment, with each experimental unit consisting of three shallot seed explants. The observed variables were the time when buds appeared, the number of leaves, the length of the leaves, and the weight of biomass. The results of the experiment showed that the concentration of 30 g sucrose/l media and 0.5 times concentration of the basic media MS is the most suitable composition for the initial growth of shallots from seeds. This was indicated by the fastest buds and the formation of the most leaves at 2 weeks after planting. The use of sucrose or MS base media, each at a concentration of 30 g sucrose/l Media or 0.5 times of concentration, was found to be suitable for the growth of shallots indicated by the longest leaf growth and the heaviest biomass.